2021
DOI: 10.4103/ijmr.ijmr_817_18
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the prevalence of endometriosis in women

Abstract: Background & objectives: Endometriosis is one of the causes of female infertility, but the prevalence of endometriosis is not exactly known. We conducted a systematic review and meta-analysis to provide an estimate of the prevalence of endometriosis in women considering the stage of disease, diagnostic method, geographical distribution, clinical symptoms and sample size. Methods: MEDLINE, Web of Science, Google Scholar, Scopus and Cumulative Index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 34 publications
1
31
0
4
Order By: Relevance
“…49 Similarly, this lack of direct correlation extends to its impact on fertility, as cases of stage four endometriosis with rectal involvement may not necessarily have a more profound effect on fertility compared to instances involving ovarian endometriomas, highlighting the intricate and multifaceted nature of the disease's influence on reproductive health. 50,51 Early evidence suggested that laparoscopic excision of any visible endometriotic lesions in early stages of the disease, seem to improve the fecundity of these women, however that does not justify aggressive surgical treatments. [52][53][54][55] Surgical management for endometriosis is usually reserved in cases of bilateral or large endometriomata, severe and/or recurrent disease and adhesions that might impact tubo-ovarian interface, or when the primary complaint is not related to fertility.…”
Section: The Impact Of Endometriosis On Fertility Performancementioning
confidence: 99%
“…49 Similarly, this lack of direct correlation extends to its impact on fertility, as cases of stage four endometriosis with rectal involvement may not necessarily have a more profound effect on fertility compared to instances involving ovarian endometriomas, highlighting the intricate and multifaceted nature of the disease's influence on reproductive health. 50,51 Early evidence suggested that laparoscopic excision of any visible endometriotic lesions in early stages of the disease, seem to improve the fecundity of these women, however that does not justify aggressive surgical treatments. [52][53][54][55] Surgical management for endometriosis is usually reserved in cases of bilateral or large endometriomata, severe and/or recurrent disease and adhesions that might impact tubo-ovarian interface, or when the primary complaint is not related to fertility.…”
Section: The Impact Of Endometriosis On Fertility Performancementioning
confidence: 99%
“…The exact prevalence of endometriosis is unknown, but approximations range from 1% to 10% [8,9]. Prevalence is much higher amongst women suffering from infertility and chronic pelvic pain, estimated to be 47% and 42%, respectively [10,11]. Unfortunately, until the accuracy of diagnostic measures improves and education among community members and HCPs increases, the exact prevalence of endometriosis will remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Dysmenorrhea is the cardinal complaint, present in approximately 50%-60% of women with endometriosis, followed by irregular and/or heavy menstrual bleeding (51%), non-menstrual chronic pelvic pain (CPP) (37%), deep dyspareunia (26%-55%), cyclical intestinal complaints (48%), cyclical urinary complaints (12%), and subfertility (12%-50%). [2][3][4][5] Globally, the prevalence of endometriosis is estimated to be 6%-10% among all women of reproductive age, 4,[6][7][8] more than 60% in women with CPP, 9 and around 30%-50% among women presenting with subfertility. 5,10 Epidemiological reports vary depending on data availability, study design and quality, diagnostic methods, accuracy of medical coding, geography, ethnicity, socioeconomic status, and other population distribution factors.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,11 One large international meta-analysis of 17 studies that analyzed more than 127 000 women reported a pooled prevalence estimate of 18% among reproductiveage women, which appeared to be skewed upward by a higher prevalence among developing countries. 6 Relatively high rates of endometriosis have also been reported among women of Asian ethnicity compared with white female populations, 6,[12][13][14][15][16][17] which is noteworthy given that the Asian region comprises approximately 60% of the world's population, 18 approximately half of whom are women. 19 A recent meta-analysis reported a significant odds ratio of 1.63 for endometriosis diagnosis in Asian versus white women.…”
Section: Introductionmentioning
confidence: 99%